Phylogeny and putative virulence gene analysis of Bartonella bovis - Tay, Sun Tee; Kho, Kai Ling; Lye, Siew Fen; Ngeow, Yun Fong (Japanese Society of Veterinary Science, 2018)
Bartonella bovis is a small Gram-negative bacterium recognized as an etiological agent for bacteremia and endocarditis in cattle. As few reports are available on the taxonomic position of B. bovis and its mechanism of virulence, this study aims to resolve the phylogeny of B. bovis and investigate putative virulence genes based on whole genome sequence analysis. Genome-wide comparisons based on single nucleotide polymorphisms (SNP) and orthologous genes were performed in this study for phylogenetic inference of 27 Bartonella species. Rapid Annotation using Subsystem Technology (RAST) analysis was used for annotation of putative virulence genes. The phylogenetic tree generated from the genome-wide comparison of orthologous genes exhibited a topology almost similar to that of the tree generated from SNP-based comparison, indicating a high concordance in the nucleotide and amino acid sequences of Bartonella spp. The analyses show consistent grouping of B. bovis in a cluster related to ruminant-associated species, including Bartonella australis, Bartonella melophagi and Bartonella schoenbuchensis. RAST analysis revealed genes encoding flagellar components, in corroboration with the observation of flagella-like structure of BbUM strain under negative straining. Genes associated with virulence, disease and defence, prophages, membrane transport, iron acquisition, motility and chemotaxis are annotated in B. bovis genome. The flagellin (flaA) gene of B. bovis is closely related to Bartonella bacilliformis and Bartonella clarridgeiae but distinct from other Gram-negative bacteria. The absence of type IV secretion systems, the bona fide pathogenicity factors of bartonellae, in B. bovis suggests that it may have a different mechanism of pathogenicity.